Prevalence of permanent teeth avulsion in a brazilian trauma center: a 12 years retrospective study - Rebouças, Pedro Diniz; Macedo-Rodrigues, Lorena Walesca; Santiago, Adriana Kelly de Sousa; Gondim, Juliane Oliveira; Moreira Neto, José Jeová Siebra (Brazilian Dental Science, 2015)
Objective: The aim of this study is to perform a retrospective study of cases of avulsion of permanent teeth in patients from 12 years of the Oraldental Trauma Center (CENTRAU) of the School of Dentistry of Faculty of Pharmacy, Dentistry and Nursing in Federal University of Ceara. Material and Methods: A retrospective transversal study characterized by direct observation of dental records was performed of a spontaneous demand sample of dental trauma victims who presented to the Oraldental Trauma Center of UFC (CENTRAU) during the period from May 2001 to May 2013 was conducted. Results: The analisys was done on 1,104 records,which 66 patients reported having been victims of avulsion with 88 avulsed permanent teeth with ages ranging between 6 and 30 years Among the 88 avulsed teeth, 59 (67.04%) were replanted. Only in 9 (15.5%) cases replantation was immediately. The storage medium that was the most widely used was the oral cavity by 8 (30.7%) patients. In 26 (39.4 %) cases, the cause of avulsion was falling to the ground. Conclusion: In this study, it was clear that cases of avulsion in CENTRAU corresponded to a low occurrence of all cases seen in the center.